Bulletin R Prati and Dr Mark Ministerial Decree No. 92/2013 Amending The Executive Regulations of Law No. 48 Of The Year 1982 Regarding The Protection Of The River Nile - egypt (2025)
Ministry of water resources and Irrigation ministerial decree 28 January 2013 amending the executive regulations of law no. 48 of the year 1982 regarding the protection of the river Nile and waterways against pollution issued as per ministerial decree no. 402 of the year 2009 – part 1: definition – part 2: licensing the establishment for discharging treated liquid wastes into waterways – part 3: the control on compliance with the conditions of the license granted to the establishment – part 4: in discharging the wastes of the stationary and movable houseboats and licensing the erection thereof – part 5: taking samples and carrying out analysis – part 6: controls, standards and specifications for the discharging of treated liquid wastes into waterways -- part 7: fees and fines proceeds fund – part 8: general provisions قرار وزارى رقم 92 لسنة 2013 بتعديل اللائحة التنفيذية للقانون رقم 48 لسنة 1982 بشأن حماية نهر النيل والمجارى لمائية من التلوث الصادرة بالقرار الوزارى رقم 402 لسنة 2009